Analyzing Students’ Numeracy Literacy in Relation to Mathematics Anxiety - Husna, Asmaul; Khatimah , Husnul (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
The growing global emphasis on numeracy as a core competency for 21st-century learners underscores the urgency of addressing mathematics anxiety, which may act as a critical barrier to students’ achievement. This study aims to analyze seventh-grade students’ numeracy literacy in relation to mathematics anxiety and to examine the association between three indicators of numeracy literacy and three levels of mathematics anxiety (low, moderate, and high). A qualitative approach was employed with six students purposively selected based on mathematics anxiety questionnaire results, consisting of two students from each anxiety level. The instruments included (1) a numeracy literacy test on two-dimensional geometry, (2) a mathematics anxiety questionnaire, and (3) a semi-structured interview protocol. Data were analyzed using Miles and Huberman’s model with triangulation to ensure validity and trustworthiness. The findings indicate that students with low mathematics anxiety successfully demonstrated all numeracy literacy indicators. In the moderate-anxiety group, one student achieved all indicators while another met only one. Students with high anxiety failed to demonstrate any indicator, suggesting that heightened anxiety hindered their mathematical performance. Theoretically, this study contributes to the growing body of literature on the interplay between affective factors and numeracy literacy by providing empirical evidence from the context of junior secondary education. Practically, the findings offer insights for teachers and policymakers to design pedagogical interventions that reduce mathematics anxiety and enhance students’ capacity for logical reasoning and problem-solving.